2009
DOI: 10.1007/s10096-008-0688-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of paradoxical effect with caspofungin in Candida albicans

Abstract: To the editor, In their article regarding the paradoxical growth effect with echinocandins, Fleischhacker et al. [1], discussing their findings with caspofungin, state: "Stevens et al. did not demonstrate [a paradoxical effect, i.e., growth in concentrations above an apparent MIC] in a … group of C. albicans isolates…," citing two of our papers [2,3]. However, in our original description of the paradoxical effect with caspofungin [2], we reported the phenomenon in two sets of C. albicans isolates, 16% of 25 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…If the lipid side chains affect membrane solubility and subsequently the activity of the drug, the local environment (cell membrane/cell wall) is predicted to influence the antifungal potency of each echinocandin to different degrees depending upon the nature of the lipid side chain. Perhaps CAS activity is most susceptible to chemical properties imparted by the fungal cell membrane/cell wall, potentially explaining differential echinocandin susceptibility in A. lentulus and the paradoxical growth effect, which is predominantly observed with CAS (7,14,16,(37)(38)(39)42). The A. lentulus GS complex isolated from the cell is sensitive to both CAS and MICA, supporting the notion that the environment of the cellular GS complex influences the effectiveness of CAS but not that of MICA.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…If the lipid side chains affect membrane solubility and subsequently the activity of the drug, the local environment (cell membrane/cell wall) is predicted to influence the antifungal potency of each echinocandin to different degrees depending upon the nature of the lipid side chain. Perhaps CAS activity is most susceptible to chemical properties imparted by the fungal cell membrane/cell wall, potentially explaining differential echinocandin susceptibility in A. lentulus and the paradoxical growth effect, which is predominantly observed with CAS (7,14,16,(37)(38)(39)42). The A. lentulus GS complex isolated from the cell is sensitive to both CAS and MICA, supporting the notion that the environment of the cellular GS complex influences the effectiveness of CAS but not that of MICA.…”
Section: Discussionmentioning
confidence: 72%
“…As noted above, the paradoxical growth of Aspergillus and Candida spp. in the presence of high levels of echinocandins is more commonly observed with CAS (7,14,16,(37)(38)(39)42), also potentially implying that the precise mechanism by which these drugs inhibit the cellular GS complex is not the same. Consistently with our conclusions, Fortwendel et al hypothesize that the paradoxical growth recovery of A. fumigatus reflects separate mechanisms that allow survival and permit radial growth in the presence of high CAS concentrations but not in ANID or MICA (16).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have reported a paradoxical effect at higher concentrations against both Candida (39) and Aspergillus (15) species. A complete understanding of this effect may advance our knowledge of fungal responses to echinocandins and improve treatment strategies.…”
mentioning
confidence: 99%
“…PG is reminiscent of the paradoxical effect observed for other cell wallactive antimicrobial agents, including beta-lactams, which is also known as the Eagle effect (10). These two in vitro susceptibility testing phenotypes are now well described (1,16,24,25). About 15% of C. albicans isolates display PG in vitro (6,11,24).…”
mentioning
confidence: 97%
“…These two in vitro susceptibility testing phenotypes are now well described (1,16,24,25). About 15% of C. albicans isolates display PG in vitro (6,11,24). PG has been observed, but not reproducibly, with some isolates in vivo (7).…”
mentioning
confidence: 99%